1988
DOI: 10.1093/nar/16.9.4077
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and hybridization of a series of biotinylated oligonucleotides

Abstract: A series of oligonucleotides containing biotin-11-dUMP at various positions were synthesized and compared in quantitative, colorimetric hybridization-detection studies. A deoxyuridine phosphoramidite containing a protected allylamino sidearm was synthesized and used in standard, automated synthesis cycles to prepare oligonucleotides with allylamino residues at various positions within a standard 17-base sequence. Biotin substituents were subsequently attached to the allylamino sidearms by reaction with N-bioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 16 publications
0
32
0
1
Order By: Relevance
“…Similarly, a previous study revealed that internal biotin labels attached via aminoallyl-dNTP subtly affect hybridization thermodynamics and duplex stability, and end-labeling of the DNA target enhances hybridization intensity (22). Nevertheless, we have shown that the carbodiimide-based cyanine dyes produce consistent data when repeatedly applied to analyses under the same conditions.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, a previous study revealed that internal biotin labels attached via aminoallyl-dNTP subtly affect hybridization thermodynamics and duplex stability, and end-labeling of the DNA target enhances hybridization intensity (22). Nevertheless, we have shown that the carbodiimide-based cyanine dyes produce consistent data when repeatedly applied to analyses under the same conditions.…”
Section: Discussionmentioning
confidence: 89%
“…The probe used in this work was labelled with biotin-7-dATP by tailing at the 3' end with terminal deoxynucleotydyl transferase [33]. We have selected this system because it allows the incorporation of an adequate number of biotin residues.…”
Section: Discussionmentioning
confidence: 99%
“…We have selected this system because it allows the incorporation of an adequate number of biotin residues. It has been shown that oligonucleotide probes with unhybridized 'tails' of biotin-dNTP residues provide a non-radioactive detection substrate that is more sensitive than one with biotin incorporated into internucleotide linkage by chemical synthetic methods [33].…”
Section: Discussionmentioning
confidence: 99%
“…01-igonucleotides can be labelled with radioisotopes (85,86), or with nonradioactive marker groups (87)(88)(89)(90) action can be improved by increasing the concentration of probe, without the danger of probe re-association, and removal from the hybridization equilibrium. The main disadvantages of oligonucleotides are, firstly, that their labelling results in probes with specific activities 10-100-fold less than those produced by random hexanucleotide priming (33,34) or nick translation (32) and, secondly, that a knowledge of the nucleotide sequence of the target nucleic acid is a prerequisite to oligonucleotide synthesis.…”
Section: Detection Of Restriction Length Polymorphisms Fragmentmentioning
confidence: 99%